PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KARAKTER RASA INGIN TAHU SISWA DALAM PEMBELAJARAN IPA DI KELAS IV SDN 15 TELAGA BIRU KABUPATEN GORONTALO - Gamar Abdullah (PEDAGOGIKA, 2020)
The problem in this study is whether there is an influence of the inquiry learning model on the character of students' curiosity in learning science in grade IV SDN 15 Telaga Biru, Gorontalo District. The aim is to determine the effect of inquiry learning models on the character of students' curiosity in science learning in grade IV SDN 15 Telaga Biru Gorontalo district. This research was conducted using the pre-experimental design method with the design of one group pretest-posttest design. The population in this study were all fourth grade students of SDN 15 Telaga Biru. Withdrawal of the sample using saturated sampling technique, which amounted to 29 people, where all members of the population made as research samples. This study uses a questionnaire as an instrument. Based on the results of the study, there is an influence of the inquiry learning model on the character of student curiosity, with the average value of the results of the character of students' curiosity in the treatment class before using the inquiry learning model which is 69, 190 and after using the inquiry learning model is 82, 328. Based on the criteria of hypothesis testing obtained t count = 7.974 and t table = 1.70 or t count> t table, in other words tcount is outside the acceptance area of the hypothesis H0 (H0 is rejected) which means accepting the alternative hypothesis (H1 accepted). This means that there is an influence of the inquiry learning model on the character of students' curiosity in science learning in grade IV SDN 15 Telaga Biru.